Zaragoza Life Project: Creation, Management and Promotion of Green Infrastructure of Zaragoza (Spain). LIFE12 ENV/ES/000567 - Montserrat Hernández Martín; Luis Manso de Zúñiga González (Fábos Conference on Landscape and Greenway Planning, 2016)
The City Hall of Zaragoza turned out to be beneficiary in the year 2012 of a European LIFE project called Life Zaragoza Natural. The general objective of the project is to protect, enhance, value, know and bring the Green Infrastructure (GI) of Zaragoza to the attention of the public, which includes Natura 2000 spaces (Sites of Community Importance (SCIs) and Special Protection Areas (SPAs)) as well as the Green Belt and other natural spaces of municipal interest to be considered of great uniqueness on European scale due to both its contiguity and proximity to a large city and its extraordinary state of conservation. This main objective is considered as a continuation of biodiversity management and environmental improvement policies held by Zaragoza City Council. It is considered as an opportunity for employment (according to "green economy" guidelines and the current economic crisis). Zaragoza is one of the largest municipal districts of Spain (nearly 1.000 Km2) Its peculiar location characterized by the passage of three rivers in a semidesert area provides the existence of exceptional natural heritage, with the coexistence of multiple landscapes. The biodiversity of approximately 40% of the municipal area is important to be preserved and is therefore protected both on Europe level, Natura 2000, and on national level. In addition, Zaragoza has an extensive network of parks, gardens and green areas which has taken a quantum and qualitative leap in the last decade in their green areas from having 3.200.000m2 to having over 8.270.000m2. Meanwhile, the General Urban Management Plan of Zaragoza establishes a classification system based on soil classification techniques (urban land, building land and undeveloped land) and rating as well as the regulation of uses, conditions for the protection and management of undeveloped land, generic or special. This is the first of instruments for the protection of natural values of the municipality. 52.000 hectares are urban protected as special undeveloped land.
Keywords: greenways; zaragoza; spain; life project; green infrastructure